Natural Frequencies of Shear Deformable Plates by Polyharmonic Splines. (3rd October 2013) - Ferreira, A. J. M.; Zenkour, A. M.
Abstract : We use the third-order shear deformation theory and a collocation technique with polyharmonic splines to predict natural frequencies of moderately thick isotropic plates. The natural frequencies of vibration are computed for various plates and compared with some available published results. Through numerical experiments, the capability and efficiency of the present method for eigenvalue problems are demonstrated, and the numerical accuracy and convergence are thoughtfully examined.